Analysis of the critical pool level of partially submerged slopes. (16th December 2019) - Wang, Wei; Griffiths, D.V.
Summary: Partially submerged c ′ − φ ′ slopes with a horizontal water table exhibit a critical pool level at which the factor of safety becomes a minimum. The phenomenon was first identified using finite element methods, but in this paper, a more thorough analytical investigation is presented. The approach described herein assumes a rigid block sliding with a circular failure mechanism, combined with optimization software to identify the critical circle. The method is initially validated against known slope solutions that assume circular and log‐spiral mechanisms and shown to give excellent agreement, especially for flatter slopes. The method is then applied to partially submerged slopes with a focus on the critical pool level. Through detailed investigation of the overturning and restoring moments in the stability analyses, the critical pool level phenomenon is shown to lie in the trade‐off between the destabilizing effects of internal pore pressures on soil strength and the stabilizing effect of external hydrostatic water pressures on the slope surface.